A rare complication following radiofrequency ablation. (18th February 2013) - Rajakulasingam, Ramyah; Francis, Rohin; Ghuran, Azad
Abstract : Atrial–oesophageal fistula (AOF) formation is a rare but often fatal complication post radio frequency ablation (RFA). Mortality ranges from 67% to 100%, with a rapid progression from symptom onset to death. We report a case of a healthy man in his early 40s who presented with a Glasgow Coma Scale  of 5/15, clinical evidence of sepsis and Streptococcus viridans bacteraemia, 14 days following uncomplicated RFA for atrial fibrillation. Establishing a diagnosis of AOF can be difficult, as patients may have bacteraemia, but are consequently misdiagnosed with infective endocarditis, as in this case. One should have a high-index of suspicion for AOF in patients presenting with the aforementioned constellation of symptoms following ablation. There are no established predictors of mortality, but prompt detection, emergent operative intervention and prolonged antibiotic therapy are vital for survival.